234k views
1 vote
Fill in each box with the correct number or variable.

6(x+8)=6. +6.
6(x + 8) = 6·+6.
(List the terms in the same order as they appear in the original list.)

User Pcampr
by
5.0k points

1 Answer

3 votes

Answer:

x = (-6)

Explanation:

6(x+8)=6+6

6(x)=6x 6(8)=48

6x + 48 = 6+6

6+6=12

6x+48=12

48 - 48+6x=12 - 48

6x=(-36)

6x/6 (-36)/6

-6

x = (-6)

User Black Lotus
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.